California Welcomes the World to the Exposition City San Francisco 1915
Note on front: Panama-Pacific International Exposition San Francisco 1915, American Resolution Successfully Grapples With The Herculean Task. Note On verso: From the exhibition: "The Panama-Pacific International Exposition" October 1982-December 1983 Lowie Museum of Anthropology University of California, Berkeley.